2022
DOI: 10.3389/fneur.2022.868051
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Stroke Unit Operational Metrics: Institutional Experience, Systematic Review and Meta-Analysis

Abstract: BackgroundThe available literature on mobile stroke units (MSU) has focused on clinical outcomes, rather than operational performance. Our objective was to establish normalized metrics and to conduct a meta-analysis of the current literature on MSU performance.MethodsOur MSU in upstate New York serves 741,000 people. We present prospectively collected, retrospectively analyzed data from the inception of our MSU in October of 2018, through March of 2021. Rates of transportation/dispatch and MSU utilization were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Considering the number of thrombolysis and thrombectomy cases, 28 thrombectomy cases and 52 thrombolysis cases per year were estimated. This is well within the range of a recent meta‐analysis evaluating the thrombolysis and thrombectomy treatments of all published MSU studies, rendering 131 (95% confidence interval 79–183) thrombolysis treatments per year and 34 (95% confidence interval 17–50) thrombectomy cases per year [ 34 ]. Because of our hypothetical approach, there are a number of unknown errors possibly interfering with our assumptions, amongst others the actual stroke incidence and its regional heterogeneity.…”
Section: Discussionsupporting
confidence: 63%
“…Considering the number of thrombolysis and thrombectomy cases, 28 thrombectomy cases and 52 thrombolysis cases per year were estimated. This is well within the range of a recent meta‐analysis evaluating the thrombolysis and thrombectomy treatments of all published MSU studies, rendering 131 (95% confidence interval 79–183) thrombolysis treatments per year and 34 (95% confidence interval 17–50) thrombectomy cases per year [ 34 ]. Because of our hypothetical approach, there are a number of unknown errors possibly interfering with our assumptions, amongst others the actual stroke incidence and its regional heterogeneity.…”
Section: Discussionsupporting
confidence: 63%
“…Expected average daily patients treated by MSU ranged from 0.55 (0.44-0.67) to 0.77 (0.61-0.92) in 8-to 16-h operation models. The rate of daily t-PA administration per MSU is expected to be 0.22 (0.18-0.26) per 24 h, which is nearly five-fold lower than the one reported by the well-established MSU service from Houston, TX (12). Whereas MSU programs in rural areas aim to expand the radius of MSU operation up to 250 km (27), in the Mannheim case with a densely populated surrounding area, simulation revealed that a limited increase in driving distance of five more minutes lead to an increase of 30-40% in patient numbers.…”
Section: Discussionmentioning
confidence: 75%
“…The estimated proportions of patients with ischemic stroke, transient ischemic attack (TIA), hemorrhagic stroke, and stroke mimics typically treated by MSU were taken from recent literature ( 9 , 10 ). MSU-specific metrics such as the number of cancelations, utilization rate, average distance and duration per dispatch, as well as the tPA administration rate were considered ( 11 , 12 ). Assuming an MSU can miss stroke cases on a dispatch-level by inaccuracy of EMS dispatchers and on an MSU-level by not being able to manage simultaneous cases at peak times and by being located too far away from a specific case.…”
Section: Methodsmentioning
confidence: 99%